2015
DOI: 10.1111/pde.12728
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Ichthyosiform Erythroderma Superimposed with Chronic Dermatophytosis: A Report of Three Siblings

Abstract: Congenital ichthyosiform erythroderma is an autosomal recessive ichthyosis characterized by severe scaling and erythroderma. We report a family of three siblings who were all born with a collodion membrane and presented with diffuse scaling and pruritus. All three children subsequently developed chronic cutaneous dermatophyte infections requiring oral antifungals. One child developed superinfection with methicillin-resistant Staphylococcus aureus requiring antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 12 publications
0
15
0
9
Order By: Relevance
“…Based on case reports and our experience, Staphylococcus aureus, dermatophyte, and candidal infections occur not infrequently in patients with ichthyosis, although S aureus infections are less common than in those with moderate-to-severe AD. 99,[112][113][114][115][116] Even with an anti-IL-17 drug (secukinumab) for psoriasis, only about 1% of patients have mild-to-moderate mucocutaneous infections, predominantly candidal. 117,118 The reactive role of T H 17/IL-23 skewing to the barrier defects versus a primary pathogenic role in patients with ichthyosis can only be clarified through future studies with targeted antagonists, which include careful monitoring for mucocutaneous infections.…”
Section: Discussionmentioning
confidence: 99%
“…Based on case reports and our experience, Staphylococcus aureus, dermatophyte, and candidal infections occur not infrequently in patients with ichthyosis, although S aureus infections are less common than in those with moderate-to-severe AD. 99,[112][113][114][115][116] Even with an anti-IL-17 drug (secukinumab) for psoriasis, only about 1% of patients have mild-to-moderate mucocutaneous infections, predominantly candidal. 117,118 The reactive role of T H 17/IL-23 skewing to the barrier defects versus a primary pathogenic role in patients with ichthyosis can only be clarified through future studies with targeted antagonists, which include careful monitoring for mucocutaneous infections.…”
Section: Discussionmentioning
confidence: 99%
“…Some forms of CI seem to be more prone to develop recurrent skins infections, including ARCIs, notably HI, epidermolytic ichthyosis (EI), Netherton syndrome (NS) and keratitis–ichthyosis–deafness (KID) syndrome . Many patients with ARCIs or KID syndrome experience recurrent dermatophytosis (e.g. from Trichophyton rubrum ).…”
Section: Complicationsmentioning
confidence: 99%
“…Kamalam et al. described tinea glabrosa and tinea manuum and unguium (onychomycosis) associated with T. rubrum in two infants with RXLI and IV, respectively [9], while CIE with T. rubrum was also frequently reported [3, 1012]. In addition to T. rubrum , T. mentagrophytes , Epidermophyton (E.) floccosum , T. tonsurans , T. verrucosum , Geomyces pannorum , and Candida (C.) albicans infections have also been recorded in patients with ichthyosis [6, 7, 13–16].…”
Section: Nonsyndromic Ichthyoses and Fungal Infectionsmentioning
confidence: 99%
“…In addition to T. rubrum , T. mentagrophytes , Epidermophyton (E.) floccosum , T. tonsurans , T. verrucosum , Geomyces pannorum , and Candida (C.) albicans infections have also been recorded in patients with ichthyosis [6, 7, 13–16]. Some patients with ichthyoses combined with extensive and recalcitrant fungal infections have also been identified [3, 7, 11, 13, 17, 18]. Advances in technology have increased research into the mechanisms of fungal infection in ichthyosis patients [19] and have suggested a correlation between genotype and susceptibility to fungal infection [20].…”
Section: Nonsyndromic Ichthyoses and Fungal Infectionsmentioning
confidence: 99%
See 1 more Smart Citation